Burn scar detection using polarimetric ALOS-2 data - Plank, Simon; Karg, Susanne; Martinis, Sandro (IGARSS 2018 - 2018 IEEE International Geoscience and Remote Sensing Symposium, 2018)
Fire is both a natural disturbance regime and a threat to infrastructure, forestry and human lives. Satellite remote sensing offers a fast and efficient way to reliably estimate the burnt area. In most cases, optical satellite data are used for burn scar detection. Nevertheless, smoke, clouds or rain can decrease the quality of classification. In these cases, SAR data can be a good alternative. Using quad-polarized SAR data, the backscatter can be decomposed into different scattering mechanisms, describing the scatterer more precisely. Here, we will present the possibilities and limitations of using quad-polarimetric ALOS-2 data for burnt area mapping using an object-based image analysis approach based on change-detection. As a case study the big fire event which affected Fort McMurray, Alberta, Canada in May/June 2016 was investigated.